The Influence of Job Performance, Social Security, and Employee Incentives on Employee Job Satisfaction (Case Study of PT. Bank Syariah Indonesia Medan S. Parman Branch Office) - Novia Sari; Sugianto Sugianto; Nurlaila Nurlaila (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
This study aims to determine the significant effect of work performance, social security, and employee incentives on job satisfaction. This research was conducted using quantitative analysis. The population in this study numbered 35, with 35 samples taken. The sampling technique in this study used a total sampling technique. This study used secondary data obtained from questionnaires. Using the Multiple Regression Analysis methods, using SPSS 22. Based on the results of the first hypothesis test, it is known that the significant value of work performance is 3.894 > 2.03951. The variable of work performance has a substantial effect on the variable of employee job satisfaction. The second hypothesis shows that social security has an essential value of 0.477 < 2.03951 means that the social security variable has no significant effect on the employee job satisfaction variable. The third hypothesis shows a powerful employee incentive, namely 2.510 > 2.03951, meaning that the employee incentive variable significantly affects the employee job satisfaction variable. The fourth hypothesis shows a significant Fcount value of 20.093 compared to Ftable of 2.90 (20.093 > 2.90), meaning that work performance variables (X1), social security (X2) and employee incentives (X3) simultaneously (simultaneously) have a significant influence with variable employee job satisfaction